1994
DOI: 10.1152/ajpregu.1994.266.6.r1824
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral naloxone attenuates lipopolysaccharide fever in guinea pigs by an action outside the blood-brain barrier

Abstract: We have previously shown that the febrile response of guinea pigs to lipopolysaccharide (LPS) is attenuated by the subcutaneous administration of the tertiary mu-receptor opioid antagonist naloxone-hydrochloride (Nal-HCl). Because Nal-HCl readily crosses the blood-brain barrier (BBB), this study was undertaken to investigate whether its effect on fever is mediated peripherally or centrally. For this, the effects of 1) Nal-HCl (23 and 46 mumol/kg sc), 2) the quaternary opioid antagonists Nal-methiodide (Nal-mI,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…Although studies revealed that central nervous system (CNS) participation is probably required for the effect intravenous opioid preconditioning [6] and not for IPC [9], there is no direct evidence to demonstrate central ORs mediates the protective effect of MPC and IPC. In this study, we intrathecally or intravenously administered naloxone methiodide (NM), a quaternary non-selective ORs antagonist, which dose not cross the blood brain barrier [10], to investigate the role of central and peripheral ORs in the cardioprotective effects of MPC and IPC.…”
Section: Introductionmentioning
confidence: 99%
“…Although studies revealed that central nervous system (CNS) participation is probably required for the effect intravenous opioid preconditioning [6] and not for IPC [9], there is no direct evidence to demonstrate central ORs mediates the protective effect of MPC and IPC. In this study, we intrathecally or intravenously administered naloxone methiodide (NM), a quaternary non-selective ORs antagonist, which dose not cross the blood brain barrier [10], to investigate the role of central and peripheral ORs in the cardioprotective effects of MPC and IPC.…”
Section: Introductionmentioning
confidence: 99%
“…POMC peptide is a precursor for several biologically active neuropeptides including ␣-MSH, ␤-endorphin, and ACTH (40). Of particular interest to the current study is ␤-endorphin as blockade of -opioid receptor, one of the receptors for ␤-endorphin either by specific antagonists or genetic mutation abrogates the fever response induced by classical pyrogens including LPS (4,5,16,44,61) via several different mechanisms, including a central hypothermic action, peripheral vasodilation, and peripheral antipyretic activity (44).…”
Section: Discussionmentioning
confidence: 99%
“…When administered to guinea pigs intravenously, the opioid antagonist, naloxone, decreased the first and suppressed the second febrile phase elicited by LPS and abolished the febrile changes evoked by interferon-␣2, TNF-␣, and IL-6 (9). Although centrally administered -opioid receptor antagonism attenuated LPS-induced fever in rats (4) but not guinea pigs (62), peripheral administration attenuated fever in both species, suggesting that circulating opioids may play a role in fever production (9,62). Given that the opioid system is upregulated in CCK 2 KO mice (58), one may have hypothesized an increased febrile response to LPS in this strain.…”
Section: Discussionmentioning
confidence: 99%